Updated guidelines for the diagnosis and management of aspergillosis - Misch, Elizabeth Ann; Safdar, Nasia (Journal of Thoracic Disease, 2016)
New guidelines for the diagnosis and treatment of infections due to Aspergillus species were published in August of 2016 by the Infectious Diseases Society of America (IDSA) (1), replacing those previously published in 2008 (2). These guidelines incorporate new data published between January 2008 and December 2014. The document provides guidance on non-culture-based diagnosis of Aspergillus infections, discourages the use of combination anti-fungal therapy for primary management, and begins to define the place in therapy for isavuconazole, a new anti-fungal drug of the azole class approved by the U.S. Food and Drug Administration (FDA) in March 2015 to treat aspergillosis and mucormycosis.